Heuristic game-theoretic equilibrium establishment with application to task distribution among agents in spatial networks. Issue 1 (2nd January 2019) - Vahidnia, Mohammad H.; Vafaeinejad, Alireza; Shafiei, Maryam
Abstract: In numerous applications such as fleet management, emergency response scheduling and moving advertisements there is a critical need for moving-agent planning in spatial networks. For agents that perform delegated tasks in a spatial network, efficient and fair scheduling is of paramount importance. In this study, we consider the planning and task distribution among such moving agents, based on the idea of pure Nash equilibria. We show at the beginning that the Nash equilibrium appears more applicable than traditional multi-objective optimisation. This issue will be challenged according to the dependency of moving agents on each other or contention among them affecting their pay-offs. Due to the high complexity of determining pure Nash equilibria, an efficient, non-deterministic, heuristic algorithm, inspired by evolutionary computations, is proposed and investigated for solving the problem in discrete spaces. Several experiments were conducted and perfectly acceptable convergence, accuracy, performance and stability were observed using this approach.